2022
DOI: 10.1021/acs.inorgchem.2c03152
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Selective MOF-Based Probe for Turn-On Luminescent Detection of Al3+, Cr3+, and Fe3+ in Solution and Test Paper Strips through Absorbance Caused Enhancement Mechanism

Abstract: Trivalent metal ions (Cr 3+ , Al 3+ , and Fe 3+ ) constitute a major section of the environmental pollutants, and their excess accumulation has a detrimental effect on health, so their detection in trace quantity has been a hot topic of research. A highly scalable 3D porous Zn-based luminescent metal− organic framework (MOF) has been synthesized by exploiting the mixed ligand synthesis concept. The strategic selection of an aromatic π-conjugated organic linker and N-rich spacer containing the azine functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 64 publications
(37 citation statements)
references
References 74 publications
0
37
0
Order By: Relevance
“…In addition, the effective encapsulation of Eu 3+ ions in Eu 3+ @NiMOF was also verified by XPS (Figure a), in which the characteristic peaks at 1135.36 and 1164.88 eV can be assigned to the 3d 5/2 and 3d 3/2 states of Eu 3+ ions (Figure b), respectively. , When coordination interaction occurs, the electrons of O atoms will shift to Eu 3+ ions, and charge dispersion will inevitably lead to an enhancement of the O atom binding energy. Thus, the high-resolution O 1s binding energy signals shifted from 531.48 eV (C–O) and 533.13 eV (CO) for NiMOF (Figure c) and to 531.66 eV (C–O) and 533.37 eV (CO) for Eu 3+ @NiMOF (Figure d), and the C–O/CO ratio changes confirmed that the introduced Eu 3+ ions were effectively encapsulated through the coordination interactions with the uncoordinated carboxyl groups, , which was also proved by the desorption experiments and IR spectra. Eu 3+ @NiMOF showed little decrease in fluorescence intensity after stirring in aqueous solution overnight, indicating that the introduction of Eu 3+ ions occurred chemically rather than by simple physical adsorption (Figure S7).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the effective encapsulation of Eu 3+ ions in Eu 3+ @NiMOF was also verified by XPS (Figure a), in which the characteristic peaks at 1135.36 and 1164.88 eV can be assigned to the 3d 5/2 and 3d 3/2 states of Eu 3+ ions (Figure b), respectively. , When coordination interaction occurs, the electrons of O atoms will shift to Eu 3+ ions, and charge dispersion will inevitably lead to an enhancement of the O atom binding energy. Thus, the high-resolution O 1s binding energy signals shifted from 531.48 eV (C–O) and 533.13 eV (CO) for NiMOF (Figure c) and to 531.66 eV (C–O) and 533.37 eV (CO) for Eu 3+ @NiMOF (Figure d), and the C–O/CO ratio changes confirmed that the introduced Eu 3+ ions were effectively encapsulated through the coordination interactions with the uncoordinated carboxyl groups, , which was also proved by the desorption experiments and IR spectra. Eu 3+ @NiMOF showed little decrease in fluorescence intensity after stirring in aqueous solution overnight, indicating that the introduction of Eu 3+ ions occurred chemically rather than by simple physical adsorption (Figure S7).…”
Section: Resultsmentioning
confidence: 99%
“…Although the Fe 3+ ion is a very important element in living organisms, 205,206 its excess leads to harmful health effects such cardiac arrest and Alzheimer's disease. 207,208 Hence, the detection and on-site monitoring of Fe 3+ ions are critical.…”
Section: Turn On Sensing Of Cationsmentioning
confidence: 99%
“…Moreover, some LMOFs with highly π-electron rich ligands prepared by the mixed ligand assembly strategy usually show exclusive luminescence properties. [60][61][62][63] Fluorene derivatives have been widely applied as luminescent materials with high fluorescence quantum yield. 64,65 In addition, as a chromogenic group, the -NH 2 group can act as a Lewis base with the ability to stabilize metal ions because of the strong interaction between the lone pair electrons of -NH 2 and the d-orbitals of metal ions.…”
Section: Introductionmentioning
confidence: 99%